Guidelines for Special Issues Training Sessions in Secondary School Peer Counselling Programs - Gougeon, Cheryl (Canadian Journal of Counselling and Psychotherapy, 2011)
This article examines the growing trend of special issues training sessions for peer counsellors. The author describes a number of training guidelines developed as a result of the Victoria Peer Counselling Centre's 1985 training program and a formal evaluation of three sessions in that program. The suggested guidelines include training in basic listening and helping skills, extended practice of these skills into special issues sessions, mutual decision-making as to which special issues will be given priority; peer counsellor input into the activités used in training; and a strong emphasis on experiential activities. The author urges trainers to closely monitor the learning experiences of each trainee, and to provide follow-up support when special issues trigger intense personal feelings for any individual. Finally, trainers must ensure that peer counsellors understand the importance of their role, particularly in cases where they must make immediate referrals.